CITRAAN DALAM PUISI âSURAT CINTAâ KARYA WS. RENDRA - RAHIMAH, ANNI (Institut Pendidikan Tapanuli Selatan, 2017)
This research is a qualitative research. The method used in this research is descriptive method to describe a phenomenon or symptoms that occur in the real condition. The data of this research is the imagery of poetry âSurat Cintaâ by WS. Rendra. Based on the findings and discussion of the imagery research on the poetry âSurat Cintaâ by WS. Rendra. The types of images that are found in this research (1) the vision there are 7 quotes in stanza I, II, III, IV, VI, VII, and VIII, (2) the hearing there are 3 quotes in stanza I, VI, and VII, (3) the tasting there is 1 quote in stanza II, (4) the motion there are 2 quotes in stanza, I, II, V, and VI